2012
DOI: 10.1038/sc.2012.35
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with early onset post-traumatic syringomyelia

Abstract: Study design: Retrospective study. Objectives: To identify factors associated with the development of early onset post-traumatic syringomyelia within 5 years of spinal cord injury. Setting: Department of Rehabilitation Medicine, Pusan National University School of Medicine, Korea. Methods: We retrospectively examined the records of 502 patients with traumatic cervical or thoracic spinal cord injury who underwent follow-up magnetic resonance imaging (MRI) examinations more than once a year for at least 5 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 21 publications
2
13
2
1
Order By: Relevance
“…Few authors have reported similar or lower (that is, 50-33%) proportions of patients with complete compared with those with incomplete SCI among patients suffering from syringomyelia. 2,9,10 In contrast to present and other results, Ko et al 2 have reported that only 49% of patients with early syringomyelia suffered from complete SCI.…”
Section: Discussioncontrasting
confidence: 52%
See 4 more Smart Citations
“…Few authors have reported similar or lower (that is, 50-33%) proportions of patients with complete compared with those with incomplete SCI among patients suffering from syringomyelia. 2,9,10 In contrast to present and other results, Ko et al 2 have reported that only 49% of patients with early syringomyelia suffered from complete SCI.…”
Section: Discussioncontrasting
confidence: 52%
“…This is in accordance with other investigations, in which there was no association between the injury level and the time to syrinx formation. 2,4,8 In contrast, some authors have observed a higher percentage of paraplegics among patients affected by syringomyelia. 9,10 In the present study, the time from SCI to syrinx formation was approximately 16 years in tetraplegic patients, compared with 7-9 years in previous reports.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations